Ultrahigh broadband absorption in metamaterials with electric and magnetic polaritons enabled by multiple materials. (April 2022) - Wang, Zhaolong; Liu, Zhen; Duan, Guihui; Fang, Leyuan; Duan, Huigao
Highlights: Broadband absorption property of metamaterials for solar energy harvesting is illustrated. Effects of material, composition, and geometry of metamaterials on broadband absorption are investigated. The mechanisms of broadband absorption are originated from both of electric and magnetic polaritons. The interaction between two different materials for nanostructures arouses the electric and magnetic polaritons. Abstract: Large amounts of studies focus on perfect absorption of metamaterials based on electric plasmon resonance. However, it still challenges a lot in total absorption of solar energy with different kinds of plasmon resonances. In this paper, we numerically study the absorption properties of a proposed plasmonic absorber based on a variety of different materials. The proposed plasmonic absorber is composed of a carbon bottom layer, a top layer with different subwavelength nanostructures, as well as a layer of Al2 O3 in between. The effects of thickness of different layers, material, height, diameter, and center distance of nanostructures on solar energy harvesting performance are numerically studied. The simulation results show that the proposed absorber exhibits excellent broadband absorption properties, and the absorptance in the wavelength range from 300 nm to 1200 nm is higher than 98.2% or even 100% in a wide wavelength range. It has been demonstrated that the nearly perfect absorption of solar energy originates from both of strong electric dipole resonance and magnetic dipole resonance due to the interaction between nanostructures made of different materials. In addition, the carbon bottom layer also contributes to the broadband absorption of electromagnetic waves. However, the geometric parameters make a big difference on the absorption property of the proposed absorber, though there is a large tolerance for the possible error during the potential fabrication process. Furthermore, the proposed absorber is almost free of the polarization of the light. Therefore, the present study provides a new physical mechanism for designing the nearly perfect absorber for solar energy harvesting submerged in water.